Understanding Trend and Cycle in Asset Values: Reevaluating the Wealth Effect on Consumption - Lettau, Martin; Ludvigson, Sydney C (American Economic Review, 2004)
Understanding Trend and Cycle in Asset Values: Reevaluating the Wealth Effect on Consumption by Martin Lettau and Sydney C. Ludvigson. Published in volume 94, issue 1, pages 276-299 of American Economic Review, March 2004